A carbon horse race: abatement subsidies vs. permit trading in Switzerland. (16th March 2021) - Hintermann, Beat; Žarković, Maja
ABSTRACT: Swiss climate policy consists of three regulatory instruments for greenhouse gas emissions reduction: A CO 2 levy, the Swiss Emissions Trading System (CH EHS) and an additional program for medium-sized plants that is labeled 'nonEHS' and consists of command-and-control elements plus a sizeable abatement subsidy. Our paper informs about this tripartite climate policy, which is unique in the international context. Second, we estimate the differential impact of the CH EHS and the nonEHS program on plants' emissions. Our empirical strategy exploits a policy change in 2013 that instituted a mandatory emissions trading system for a subset of previously regulated plants. We find that the nonEHS outperforms the CH EHS for a minority of plants, but that on average, the two programs result in similar abatement efforts despite very different financial incentives. Plants that previously engaged in abatement efforts continue to do so even after the financial incentives were reduced by an order of magnitude. Key policy insights We find similar pollution abatement for plants regulated by an emissions trading system relative to plants receiving an abatement subsidy in Switzerland This is surprising given that the allowance price in the CH EHS is an order of magnitude lower than the abatement subsidy Emissions reductions in the ETS are especially pronounced for large plants, and for plants that had engaged in significant abatement in the past